Engagement in its Multiple Dimensions: Empathy and COLTs: Pathways to Cognitive, Affective and Behavioral Growth - Karabatsos, Ioanna (Apprendre et enseigner aujourd’hui, 2025)
Engagement in the classroom is a complex and multifaceted concept that encompasses a dynamic interplay of cognitive, affective, and behavioral dimensions. In secondary education, especially within ESL (English as a Second Language) contexts, fostering genuine engagement requires implementing diverse strategies that effectively reach students on multiple levels intellectually, emotionally, and socially. This article examines how Collaborative Learning Techniques (COLTs)—specifically Think-Pair-Share, Jigsaw, Role-Play, and Case Studies – are powerful tools to promote engagement across these interconnected dimensions. Drawing on classroom practice, empirical research, and pedagogical theories, it demonstrates how adopting an empathy-centered pedagogy can nurture deep thinking, emotional connection, and active participation among students. Ultimately, the article emphasizes that engagement should not be viewed as a fleeting outcome but as an ongoing, evolving process that flourishes when classroom environments prioritize inclusion, collaboration, emotional safety, respect and the competencies of Social and Emotional Learning (SEL).